Chemical analysis using miniaturized and Portable 3D printed systems: Where are we now? - Perrucci, Miryam; Ali, Imran; Mansour, Fotouh R.; Ulusoy, Halil I.; Ulusoy, Songül; Kabir, Abuzar; Abollino, Ornella; Giacomino, Agnese; Inaudi, Paolo; Locatelli, Marcello; Ricci, Erika Maria (Journal of Chromatography Open, 2025)
•Capillary and nano LC have emerged as exemplary techniques in GAC field.•Overview of the challenges and advancements achieved in the miniaturization.•Advancements for micro-columns, detectors, lab-on-chip, 3D printing technologies. With the growing emphasis on green chemistry (GC) and green analytical chemistry (GAC), significant efforts have been directed toward minimizing sample size and simplifying sample preparation procedures. Concurrently, ongoing research has enabled the miniaturization of instrumental configurations used for quantitative analysis, aligning with the principles of sustainability. One major challenge lies in the inherent complexity of liquid chromatography systems, which comprise multiple interconnected components. Each component has been subject to miniaturization, with careful attention to preserving analytical sensitivity, selectivity, and accuracy when applied to real samples. Interest in miniaturized systems is further fueled by the theoretical principle that reducing flow rates enhances the surface-to-volume ratio, thereby improving detection sensitivity. Building on this theoretical foundation—particularly the goals of portability, efficient sampling, and on site analysis—innovative approaches such as microfluidics and 3D printing have been employed to develop compact fluidic systems. These technologies not only broaden the scope of liquid chromatography but also open new frontiers, such as drug testing on engineered tissues, and the development of new devices suitable for space missions. This review aims to present a comprehensive overview of the challenges encountered and the advancements achieved in the miniaturization of instrumental setups and portable systems, encompassing both pre- and post-analytical stages. Furthermore, a discussion on 3D technologies available for LC-chip and miniaturized systems was also presented. [Display omitted]